Ionic liquid silver salt complexes for propene/propane separation - Agel, Friederike; Pitsch, Fee; Krull, Florian Felix; Schulz, Peter; Wessling, Matthias; Melin, Thomas; Wasserscheid, Peter (Physical Chemistry Chemical Physics, 2010)
Properties of the room-temperature liquid complex salt [Ag(propene)x][Tf2N] have been studied to probe its suitability for acting as active separation layer in immobilised liquid membrane (ILM) concepts for propane/propene separation. The pressure/temperature range of complex formation has been determined and the thermal properties of Ag[Tf2N] and [Ag(propene)x][Tf2N] have been studied by DSC (differential scanning calorimetry) and TGA (thermogravimetric analysis) measurements. Pressure dependent measurements of solubility and diffusivity showed that the observed membrane selectivity is dominated by the solubility selectivity. The self-diffusion coefficient of propene is always smaller compared to propane as propene is temporarily bound to the silver ion in the [Ag(propene)x][Tf2N] ionic liquid.